Distributed photovoltaic systems in Algeria and control of DC-DC converters for grid integration - an overview. (October 2017) - Amrouche, Said Ould; Saidj, Sabah Hana; Boumechta, Samer; Arab, Amar Hadj; Abdeladim, Kamel; Bouchakour, Salim; Yassaa, Noureddine
Abstract: This paper describes the current situation of the renewable energies (RE) in Algeria and the structure of the national grid. In view of studying the issues of grid integration of injection of renewable energy produced by distributed systems. The main issues to be considered actually in Algeria are the lines upgrade and the protections design, to prepare the near future of large share of renewable electricity in the national energy mix. For grid integration, due to continuously decreasing cost of battery storage, the modeling and the structure of control of a photovoltaic grid connected system is given.